2016
DOI: 10.1074/jbc.m116.715615
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei Methylthioadenosine Phosphorylase Protects the Parasite from the Antitrypanosomal Effect of Deoxyadenosine

Abstract: Trypanosoma brucei causes African sleeping sickness for which no vaccine exists and available treatments are of limited use due to their high toxicity or lack of efficacy. T. brucei cultivated in the presence of deoxyadenosine accumulates high levels of dATP in an adenosine kinase-dependent process and dies within a few hours. Here we show that T. brucei treated with 1 mM deoxyadenosine accumulates higher dATP levels than mammalian cells but that this effect diminishes quickly as the concentration of the deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…2B). The concomitant reduction in the ATP pool, which was previously observed with deoxyadenosine-treated and Ara-A-treated trypanosomes (11,12), was only modest in the case of FANA-A, indicating that this is probably not a significant factor contributing to the growth inhibition, which occurs at FANA-A concentrations much lower than those needed to reduce ATP levels. A radioactive tracer experiment showed that FANA-A blocked nucleic acid biosynthesis in the parasites (Fig.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…2B). The concomitant reduction in the ATP pool, which was previously observed with deoxyadenosine-treated and Ara-A-treated trypanosomes (11,12), was only modest in the case of FANA-A, indicating that this is probably not a significant factor contributing to the growth inhibition, which occurs at FANA-A concentrations much lower than those needed to reduce ATP levels. A radioactive tracer experiment showed that FANA-A blocked nucleic acid biosynthesis in the parasites (Fig.…”
mentioning
confidence: 78%
“…TbMTAP assays were performed as described previously with the recombinantly expressed and purified enzyme (11). Briefly, the enzyme was diluted in a buffer containing 50 mM potassium acetate, 50 mM Tris-HCl (pH 7.4), and 0.05% Tween 20 prior to use in the enzyme assay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations